Fully Deep‐UV Transparent Thin Film Transistors Based on SrSnO3 - Jihoon Seo; Juhan Kim; Jae Ha Kim; Jae Hoon Kim; Kookrin Char (Advanced Electronic Materials, 2024)
Abstract Ultra‐wide bandgap semiconductors are gaining attention for their promising properties for UV optoelectronics and UV transparent electronics as well as high‐power applications. Among them, La‐doped SrSnO3 exhibits excellent properties both for deep‐UV transparent oxide semiconductors and deep‐UV transparent conducting oxide. Here, the demonstration of thin film transistors (TFTs) with full deep‐UV transparency is reported, including electrodes, gate oxide, and substrate. The lightly La‐doped SrSnO3 for the channel layer is grown on MgO (100) substrates with buffer layers by pulsed laser deposition. TFTs with a metal—insulator–semiconductor structure are fabricated using high‐k perovskite dielectric LaScO3 as the gate oxide. A degenerately La‐doped SrSnO3 is used as the gate, the source, and the drain electrodes to obtain good ohmic contact with the channel layer as well as UV transparency. The resultant device shows a field effect mobility value of ≈24 cm2 V−1 s−1 and an on/off ratio >106. The optical transmittance of the entire device (including the substrate) is found to be >75% at 300 nm in wavelength. Furthermore, the electrical characteristics of the device exhibit excellent stability under visible irradiation. This research highlights the potential of SrSnO3 in advancing the field of UV optoelectronics and UV transparent electronics.